Corticostriatal and Thalamostriatal Synapses Have Distinctive Properties - Ding, Jun (Society for Neuroscience, 2008)
The two principal excitatory glutamatergic inputs to striatal medium spiny neurons (MSNs) arise from neurons in the cerebral cortex and thalamus. Although there have been many electrophysiological studies of MSN glutamatergic synapses, little is known about how corticostriatal and thalamostriatal synapses differ. Using mouse brain slices that allowed each type of synapse to be selectively activated, electrophysiological approaches were used to characterize their properties in identified striatopallidal and striatonigral MSNs. At corticostriatal synapses, a single afferent volley increased the glutamate released by a subsequent volley, leading to enhanced postsynaptic depolarization with repetitive stimulation. This was true for both striatonigral and striatopallidal MSNs. In contrast, at thalamostriatal synapses, a single afferent volley decreased glutamate released by a subsequent volley, leading to a depressed postsynaptic depolarization with repetitive stimulation. Again, this response pattern was the same in striatonigral and striatopallidal MSNs. These differences in release probability and short-term synaptic plasticity suggest that corticostriatal and thalamostriatal projection systems code information in temporally distinct ways, constraining how they regulate striatal circuitry.